KOMPOSISI JENIS POHON DAN STRUKTUR TEGAKAN HUTAN MANGROVE DI DESA PANTAI BAHAGIA KECAMATAN MUARA GEMBONG KABUPATEN BEKASI PROVINSI JAWA BARAT - Bagas Marsudi; Ombo Satjapradja; Messalina L Salampessy (Forestry Study Program University Of Mataram, 2018)
Mangrove forest ecosystems have a very important role for humans and the environment, so to prevent further damage needs to be done identification of tree species composition and structure of mangrove forest stands. For the purpose of this research is to know the composition of tree species from the level of seedling to the tree and to know the structure of its stand. Data collection methods used are Inventory of mangrove species using Indonesian mangrove determination keychain and data analysis by calculating important value index, Diversity index, relative frequency and horizontal structure analysis. The results showed that the largest tree density structure was Rhizophora mucronata of 225 trees / hectare, Avicennia marinna of 145 trees / hectare, Sonneratia alba of 65 trees / hectare and Avicennia officinalis of 65 trees / hectare and had only one crown layer namely strata A which is dominated by Rhizophora mucronata tree which has an average free height of 9 m branch with total height 12 m and diameter 29 cm. For this reason, planting efforts need to be increased to increase the number and composition for coastal protection.